(untitled) (Revista Paradigma, 2022)
The general objective of the research is the investigation of the phenomenon in intersexuality and the practice of surgical mutilation of newborns and children as a conduct contrary to human rights. The choice of the theme is justified due to its theoretical, practical and current relevance, especially with regard to the naturalization of binarism, which occurred from the violation of the rights to freedom, self-determination, life, health, autonomy and dignity of intersex subjects, facing the unilateral decision of its parents to perform sexual mutilation surgery under medical guidance. Intersexuals are born with biological characteristics that make it difficult to fit into one of the gender stereotypes (female or male). As a result, they undergo, at a young age, surgeries to “normalize” the bodies, which have been harshly questioned for being medically superfluous and bodily mutilating. The research is predominantly bibliographic and documentary and the methodologies adopted were deductive and critical-dialectic. The study led to the conclusion that, from the perspective of international human rights law, surgical interventions to “normalize” sex are true discriminatory practices and should be prohibited in all states. In addition to damaging the free development of the personality, such surgeries undoubtedly violate human rights, and can only be admitted when the intersexual has reached an appropriate stage of development and can express their free, prior and informed consent.